'You're not going to give a monkey's chuff': exploring co-production in the design of services for women who have experienced sexual violence. (July 2022) - Warwick-Booth, L; Cross, R; Coan, S; Fisher, P
Aims: Co-production is an emerging field in public health practice. We aim to present evidence of what works well to support co-production and what can be improved based upon learning from our evaluation of a co-production project implemented by Rape Crisis England and Wales (RCEW). RCEW designed and delivered a national co-production project called Weaving the Web, to inform the development of an online support service for women who have experienced sexual violence. Methods: We qualitatively evaluated the RCEW co-production approach. The specific objectives of our evaluation were to assess the increased role and voice for women and girls in co-producing services and provide better quality of evidence for what works in empowering women and girls. The evaluation was conducted in two phases: Phase 1 was the observation of co-production events ( n = 8), with findings from this used to develop an interview schedule for Phase 2, where semi-structured interviews ( n = 26) were conducted with a range of stakeholders (staff, partners and service users). Results: Staff supporting the co-production project were highly committed to the work, investing time, money, and preparation, and having a good understanding of co-production. Service users were less familiar with the approach and felt alienated by some of the language used. Most service users described participation as empowering and, in some instances, important in their own recovery. They were keen to stay involved beyond the creation of the online resource. Conclusion: The data from our evaluation illustrate that co-production on a national level is challenging. While RCEW used values-based practice, and provided a supportive culture to underpin the co-production of their online service, transformative engagement and true participation were not achieved. Learning from this project is drawn out here to outline transferrable lessons for practitioners intending to use models of co-production in other public health settings.